2015
DOI: 10.1016/j.celrep.2015.10.042
|View full text |Cite
|
Sign up to set email alerts
|

A Small Molecule that Induces Intrinsic Pathway Apoptosis with Unparalleled Speed

Abstract: Apoptosis is generally believed to be a process that requires several hours, in contrast to non-programmed forms of cell death that can occur in minutes. Our findings challenge the time-consuming nature of apoptosis as we describe the discovery and characterization of a small molecule, named Raptinal, which initiates intrinsic pathway caspase-dependent apoptosis within minutes in multiple cell lines. Comparison to a mechanistically diverse panel of apoptotic stimuli reveals Raptinal-induced apoptosis proceeds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
67
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(75 citation statements)
references
References 45 publications
8
67
0
Order By: Relevance
“…Cells were treated with 1 µM of staurosporine for 24 h or with 13 µM of raptinal(37) for 3 h as positive control, DMSO as negative control and indicated concentrations of PAC-1 and vemurafenib for 0, 2, 4, 7, 10, 12, 16, 20 or 24 h. Plates were then assessed for caspase-3/7 activity via addition of bifunctional lysis and activity buffer (200 mM HEPES, 400 mM NaCl, 40 mM DTT, 0.4 mM EDTA, 1% Triton-X, pH 7.4) with 20 µM of Ac-DEVD-AFC (Cayman Chemicals) as the fluorogenic substrate (λ ex =400 nm, λ em =505 nm). Plates were pre-incubated at 37 °C at 30 min in the Synergy multi-mode reader (BioTek) then read for 30 min at 3 min intervals.…”
Section: Methodsmentioning
confidence: 99%
“…Cells were treated with 1 µM of staurosporine for 24 h or with 13 µM of raptinal(37) for 3 h as positive control, DMSO as negative control and indicated concentrations of PAC-1 and vemurafenib for 0, 2, 4, 7, 10, 12, 16, 20 or 24 h. Plates were then assessed for caspase-3/7 activity via addition of bifunctional lysis and activity buffer (200 mM HEPES, 400 mM NaCl, 40 mM DTT, 0.4 mM EDTA, 1% Triton-X, pH 7.4) with 20 µM of Ac-DEVD-AFC (Cayman Chemicals) as the fluorogenic substrate (λ ex =400 nm, λ em =505 nm). Plates were pre-incubated at 37 °C at 30 min in the Synergy multi-mode reader (BioTek) then read for 30 min at 3 min intervals.…”
Section: Methodsmentioning
confidence: 99%
“…For reasons that remain poorly understood, cell death kinetics vary considerably between lethal stimuli, cell lines and cell death pathways, as well as between individual cells within the same population (Bernheim et al, 1977; Biton and Ashkenazi, 2011; Dixon et al, 2012; Lu et al, 2014; Shimizu et al, 2004; Spencer et al, 2009; Vanden Berghe et al, 2010). A major goal of the present work was to develop means to quantify this variability in cell death kinetics at the population level, as this knowledge may enhance our understanding of different lethal pathways, improve the classification of lethal perturbations and help identify new drugs that act through unique mechanisms (Grootjans et al, 2016; Hafner et al, 2016; Harris et al, 2016; Palchaudhuri et al, 2015; Tyson et al, 2012). …”
Section: Introductionmentioning
confidence: 99%
“…A landmark research by Paul Hergenrother and his team (Nature Clinical Biology) nearly found a way around this natural biological process that kick starts apoptosis [7]. They found a synthetic molecule that directly activates procaspase-3 to caspase-3 thus initiating apoptosis in the tumour.…”
Section: Can a Cancer Cell Be Tricked Into Dying By Using The Mechnismentioning
confidence: 99%
“…So it was postulated that therapy could be tailored to the cancer, the organ and patient's condition by measuring the levels of pro-caspase-3. This selective treatment was expected to minimize collateral damage and toxic effects of chemotherapy [5][6][7].…”
Section: Can a Cancer Cell Be Tricked Into Dying By Using The Mechnismentioning
confidence: 99%
See 1 more Smart Citation